MINAT PETANI DALAM BUDIDAYA NILAM DI DESA LAMBANGI KECAMATAN KOLONO TIMUR KABUPATEN KONAWE SELATAN - Resimiati, Resmiati; Abdullah, Sukmawati; Buana, Tjandra (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
Patchouli (Pogostemon cablin Benth) is a high-value plantation commodity that is Indonesia's primary producer of essential oils with considerable export prospects. However, despite its cultivation in various areas, including Lambangi Village in South Konawe Regency, the management of this crop continues to face challenges, such as declining soil fertility and suboptimal farmer income. The objective of this study is to ascertain the level of interest among farmers in Lambangi Village regarding the cultivation of patchouli. The population under study comprised all 30 patchouli farmers in Lambangi Village. The sample was determined using the census method. The data were processed using the class interval formula and then analyzed using descriptive analysis. The results of the study indicate that the level of interest among farmers in Lambangi Village in cultivating patchouli is relatively high, with 86.67% of farmers falling into the "good" category. The dimensions of desire, involvement, and interest exhibited a significant contribution to farmers' decisions to continue developing patchouli farming. The findings suggest that intrinsic motivation, particularly internal drive and satisfaction with cultivation outcomes, plays a pivotal role in business sustainability. Furthermore, social interaction among farmers plays a pivotal role in enhancing knowledge transfer and fostering local innovation.